Governança Pública e Eficiência das Universidades Federais Brasileiras, sob a ótica da Teoria da Agência - Pasquali, Josiane Costa (2021)
The study objective is to analyze the contribution of public governance practices to the efficiency of Brazilian federal universities, from the perspective of the Agency Theory. Because of the asymmetry of information observed in the principal-agent relationship, agency problems arise. The adoption of governance mechanisms is related to the mitigation of these problems, through monitoring and control structures, improving the institution's management and supervision, thus contributing to its efficiency. The research has a quantitative focus, initially is utilized the Data Envelopment Analysis (DEA) method to measure the efficiency of institutions; then, the Malmquist index is used to assess the variation in the efficiency of institutions from 2017 to 2018. Finally, to analyze the contribution of the adoption of governance mechanisms to the efficiency of universities, a multiple regression model was applied, having as independent variables the components of the TCU Public Governance index: Leadership; Strategy and Accountability, and as a dependent variable the Efficiency Score calculated from the application of DEA. The study results showed that for the period 2017 to 2018, no statistically significant relatio nships were found between the level of adoption of public governance practices and the efficiency of Brazilian federal universities. It was also verified, from the application of Pearson's correlation, a trend of negative correlation between the efficiency score of universities and the Governance variables: Leadership, Strategy and Accountability for 2017 data and Leadership and Accountability in 2018.